Monument for the commemoration of the founding of the Austrian republic. Fr.l.t.r.: Reumann, Adler and Hanusch - Bauer, Theo (1928)
Monument for the commemoration of the founding of the Austrian republic. Fr.l.t.r.: Reumann, Adler and Hanusch.